Triclinic form of bis{di-mu-hydroxidobis[fac-aquatribromidotin(IV)]} heptahydrate - De Lima, G.M.; Howie, R.A.; Tiekink, E.R.T.; Wardell, J.L.; Wardell, S.M.S.V. (International Union of Crystallography, 2010)
The asymmetric unit of the title hydrate, 2[Sn(H2O)(2)(OH)(2)Br-6]center dot 7H(2)O, comprises two [Br-3(H2O) Sn(mu-OH)(2)SnBr3(OH2)] units, but three independent molecules as two of these are disposed about inversion centres, and seven water molecules. In common with the monoclinic polymorph [Howie et al. (2005). Inorg. Chim. Acta, 358, 3283-3286], each of the dinuclear species features a central Sn2O2 core, distorted octahedral Sn atom geometries defined by a Br3O3 donor set, and an anti-disposition of the coordinated water molecules. In the crystal, O-h-H center dot center dot center dot O-w, O-a-H center dot center dot center dot O-w, O-w-H center dot center dot center dot O-w, and O-w-H center dot center dot center dot Br (h = hydroxyl, a = aqua, w = water) hydrogen-bonding interactions generate a three-dimensional network.